Seaweed as a sustainable food alternative: A case study of Canadian consumer behaviour - Mohamed Bilal Basha; Fazli Wahid; Gail AlHafidh; Abdul Ghafar; Parvez Akthar (Food Chemistry Advances, 2025)
This aim of this paper is to evaluate consumer attitude, behaviour, and purchase intention towards seaweed food products in Toronto, Canada to gain insight into their current market position. The study is descriptive and exploratory in nature. A multi-stage sampling procedure was used with a total of six hundred adult respondents participating. The key variables assessed in the study include health consciousness, environmental factor, taste factor, preference towards innovative diets, barriers in the consumption of seaweed food products, attitude toward seaweed consumption, behavioural intention, and purchase intention toward seaweed foods. SPSS.25 software was used to clarify and analyse the data collected from the respondents, in addition to: Descriptive statistics, Cronbach's Alpha Reliability Analysis, Exploratory Factor Analysis, Pearson Bivariate Correlation, and Independent Sample t-test. The results of the study provide convincing evidence reflecting a positive consumer attitude towards seaweed products in Toronto, Canada. Key indicators from this paper will serve to inform market stakeholders within the food and beverage industry, health and fitness industry and agricultural industry.